Migrasi Database dari CDS/ISIS ke SLIMS - Muhamad, Hamim (Pustakaloka, 2012)
CDS-ISIS is a library software developed by UNESCO, to help library managers in developing countries that less budget to develop it.In accordance with the need fast access on data and the flexible data sharing bears an idea to build library software. Slims _Senayan Library Information Management is open source software (OSS) based web.